Indirect influence of soil enzymes and their stoichiometry on soil organic carbon response to warming and nitrogen deposition in the Tibetan Plateau alpine meadow - Xuemei, Xiang; Kejia, De; Weishan, Lin; Tingxu, Feng; Fei, Li; Xijie, Wei (Frontiers in Microbiology, 2024)
Despite extensive research on the impact of warming and nitrogen deposition on soil organic carbon components, the response mechanisms of microbial community composition and enzyme activity to soil organic carbon remain poorly understood. This study investigated the effects of warming and nitrogen deposition on soil organic carbon components in the Tibetan Plateau alpine meadow and elucidated the regulatory mechanisms of microbial characteristics, including soil microbial community, enzyme activity, and stoichiometry, on organic carbon components. Results indicated that both warming and nitrogen deposition significantly increased soil organic carbon, readily oxidizable carbon, dissolved organic carbon, and microbial biomass carbon. The interaction between warming and nitrogen deposition influenced soil carbon components, with soil organic carbon, readily oxidizable carbon, and dissolved organic carbon reaching maximum values in the W0N32 treatment, while microbial biomass carbon peaked in the W3N32 treatment.Warming and nitrogen deposition also significantly increased soil